Measuring Total Factor Productivity Using the Enterprise Surveys : A Methodological Note - Francis, David C.; Karalashvili, Nona; Maemir, Hibret; Rodriguez Meza, Jorge (World Bank, Washington, DC, 2020)
Total factor productivity is a key element of economic growth and an important performance metric for policy makers. This note describes the methodology for measuring firm-level total factor productivity using the World Bank's Enterprise Surveys cross-country data. It also presents some estimates recovered from the production function. Two versions of the production function are estimated: one Cobb-Douglas, the other a more flexible translog specification. Both estimations are at the two-digit industry level pooling all the Enterprise Surveys data across economies. Evidence is found against using a Cobb-Douglas specification, which is more parsimonious, and in favor of using the flexible translog specification. The resulting firm-level estimates are all published in the Enterprise Surveys database with a unique firm identifier to link to the rest of the Enterprise Surveys data; because the estimates are reliant on new data, they are updated periodically as new Enterprise Surveys data become available. The results show that: (i) median firms operate close to constant returns to scale; (ii) gross-output and value-added production functions provide similar ranking of sectors in terms of output elasticities, capital intensity, and returns to scale; (iii) there is large, firm-level heterogeneity in output elasticities; and (iv) gross-output-based total factor productivity measures are less dispersed than the value-added ones.